1977
DOI: 10.2307/1936917
|View full text |Cite
|
Sign up to set email alerts
|

Competition and Nest Spacing in a Tropical Stingless Bee Community

Abstract: The density and dispersion patterns of nests of 5 stingless bee species are described for a tract of Costa Rican tropical dry forest. Features of suitable nest sites are analyzed, but it does not appear that nest site availability limits colony density or determines colony dispersion. Rather, food limitation is suggested by a linear relationship between the logarithm of colony biomass and the logarithm of foraging "home range." Colonies were uniformly dispersed intraspecifically in 4 species. The pattern in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
96
3
9

Year Published

1984
1984
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(112 citation statements)
references
References 12 publications
4
96
3
9
Order By: Relevance
“…Tree species for nesting In accordance with the findings of Hubbell & Johnson (1977) and Roubik (1989), many stingless bees are opportunists in their use of tree cavities for nesting. This study shows that stingless bees nests can be found in different tree species, however, more than 75.0% of nests were found in two tree species.…”
Section: Discussionsupporting
confidence: 59%
“…Tree species for nesting In accordance with the findings of Hubbell & Johnson (1977) and Roubik (1989), many stingless bees are opportunists in their use of tree cavities for nesting. This study shows that stingless bees nests can be found in different tree species, however, more than 75.0% of nests were found in two tree species.…”
Section: Discussionsupporting
confidence: 59%
“…Because the frequency of Meliponini nests inside the forest is usually low (Michener 1946;Hubbell & Johnson 1977;Oliveira et al 1995), we hypothesize that some nests may be just as isolated from the others in the same sampling area as from others located in different sampling areas. In this way, the succession of massive and rapid flowering events at the various locations where the bees are present would explain the existence of pots of distinct nests being grouped in one set and pots from the same nests not being grouped (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…O comportamento agressivo e monopolista de espécies de Trigona verifi cado neste trabalho, já era conhecido (Johnson & Hubbell 1974, Hubbell & Johnson 1977. Operárias de T. spinipes forrageiam em "bando", várias operárias monopolizando as fl ores (Almeida & Laroca 1988, Sazima & Sazima 1989, apresentam vôo lento e mimetizam vespas e abelhas agressivas que possuem acúleos desenvolvidos, como espécies de Tetrapedia e Paratetrapedia (Kerr 1951).…”
Section: Discussionunclassified